GITA SEWANA: Strategi Penciptaan Musik pada Masa Pandemi - Arsana, I Nyoman Cau (Institut Seni Indonesia Yogyakarta, 2022)
ABSTRACT On December 2, 2020, the Department of Ethnomusicology, Faculty of Performing Arts, ISI Yogyakarta, showcased faculty works entitled